2016
DOI: 10.1021/acsami.6b01636
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Natural Antioxidants by Silk Biomaterials

Abstract: The stabilities of three natural antioxidants, vitamin C (VC), (-)-epigallocatechin gallate (EGCG), and curcumin, in silk films were examined and mechanisms of stabilization were elucidated. The antioxidants were physically incorporated into three types of silk films: as-cast, dried from hydrogels, and methanol-treated. Films were stored at 4, 37, and 45 °C for 30 days in phosphate-buffered saline, pH 7.4, along with controls consisting of free antioxidants. Incorporation of antioxidants did not significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Epigallocatechin gallate (EGCG), a major component of green tea catechins, possesses diverse biological properties, including antioxidant, anti‐inflammatory and anticarcinogenic effects , and has some therapeutic effects for hyperglycaemia‐induced embryopathy, breast tumours and Alzheimer's disease correlated with oestrogen depletion . Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigallocatechin gallate (EGCG), a major component of green tea catechins, possesses diverse biological properties, including antioxidant, anti‐inflammatory and anticarcinogenic effects , and has some therapeutic effects for hyperglycaemia‐induced embryopathy, breast tumours and Alzheimer's disease correlated with oestrogen depletion . Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG), a major component of green tea catechins, possesses diverse biological properties, including antioxidant, anti-inflammatory and anticarcinogenic effects [21,22], and has some therapeutic effects for hyperglycaemia-induced embryopathy, breast tumours and Alzheimer's disease correlated with oestrogen depletion [22][23][24]. Zhao et al [25] have demonstrated that the combination of EGCG with b-lactams revealed a synergistic antibacterial effect on methicillin-resistant S. aureus (MRSA).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to synthetic polymers based on chemical reactions, silkworm silk is a protein‐based material produced by silkworms at ambient conditions in an all‐aqueous reaction environment. Silk is thus produced in an environment‐friendly process, and due to biocompatibility and mechanical features shows potential for developing healthcare products, biomedical devices, and biosensors . The extraordinary mechanical properties of silk originate from the unique highly repetitive sequence in fibroin, along molecular self‐assembly and organization at nanoscale .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lou et al (2016) used fibroin to stabilize vitamin C, curcumin, and epigallocatechin gallate. The results indicated that these antioxidants presented improved environmental stabilities of up to 14 days due to the binding of antioxidant molecules to the hydrophobic or the hydrophilic/hydrophilic boundary regions of silk [174]. Despite this work not being directly focused on CRC, it is highly relevant because antioxidants can easily react with air and other environmental conditions, losing their ROS -scavenging properties, prior to be consumed by the patient; without stabilization, the antioxidant simply will have little or no effect in the patient.…”
Section: Gonzálezmentioning
confidence: 99%